Long-lived room temperature phosphorescence of organic–inorganic hybrid systems. Issue 8 (12th March 2021) - Wang, Hua-Rui; Yang, Xiao-Gang; Qin, Jian-Hua; Ma, Lu-Fang
Abstract : This review highlights the important role of several organic–inorganic hybrid systems. The fundamental mechanism, design principles, and enhancement strategies to achieve high performance room temperature phosphorescence have been discussed. Abstract : Molecule-based crystalline materials with long-lived room temperature phosphorescence have been paid tremendous attention due to their promising properties for the critical requirements of applications in anti-counterfeiting, organic light-emitting diodes, displays, and biochemistry. It is illustrated that the room temperature phosphorescence properties of molecular phosphors can be highly enhanced based on the formation of a rigid environment. In this review, the important role of several rigid organic–inorganic hybrid hosts such as metal–organic frameworks (MOFs), organic–inorganic hybrid perovskites, and layered double hydroxides is highlighted. The fundamental mechanism, design principles, and enhancement strategies to achieve high performance phosphorescent emission have also been discussed. Finally, we briefly discuss perspectives on the further development of these organic–inorganic hybrid systems.